Oreogrammitis translucens, a new species of fern polypodiopsida: Grammatidaceae) from maliau basin conservation area, Sabah, Malaysia ((Oregrammitis translucens Suatu Species Baru Paku-pakis (Polypodiopsida: Grammitidaceae) dari Kawasan Pemuliharaan Lembangan Maliau, Sabah, Malaysia)) - Parris, B.S; Jaman., R; Latiff, A (Universiti Kebangsaan Malaysia, 2012)
A new species of fern, Oreogrammitis translucens, is described and illustrated from Maliau Basin Conservation Area, Sabah, Malaysia.